Pengaruh Penggunaan Sarana Belajar Terhadap Pelajaran PAK - Rodianus (Sekolah Tinggi Teologi Borneo, 2023)
Abstract: The effect of the use of teaching aids in learning such as LCD projectors, reference books, computers, and so on can encourage students 'memory, train students' imagination, the atmosphere of students is more active in learning, arouse students 'optimism in learning, can affect students' attention in learning , mastery of the class can be controlled properly so that this varied learning model can influence the achievement of effective learning goals. The purpose of this paper is to find out what tools can be used to increase the value of students in the subject of Christian Religious Education and find out the influence of teaching aids on increasing the value of students on the subject of Christian Religion.Keywords: Use of facilities, learning, lesson Christian educationAbstrak: Pengaruh penggunaan sarana dalam belajar seperti, LCD Proyektor, buku referensi, computer, dan sebagainya dapat mendorong daya ingat siswa, melatih daya imajinasi siswa, suasana siswa lebih aktif dalam belajar, membangkitkan rasa optimis siswa dalam belajar, dapat mempengaruhi perhatian siswa dalam belajar, penguasaan kelas dapat dikendalikan dengan baik sehingga model belajar yang bervariasi ini dapat mempengaruhi tercapainya tujuan belajar yang efektif. Adapun tujuan dalam penulisan ini adalah untuk mengetahui sarana apa saja yang dapat di gunakan untuk meningkatkan nilai siswa pada mata pelajaran Pendidikan Agama Kristen dan mengetahui pengaruh sarana apa saja yang dapat dipakai terhadap peningkatan nilai siswa pada mata pelajaran Agama Kristen.Kata kunci: Pengaruh, sarana belajar, pelajaran, Pendidikan Agama Kristen